Nanofiltration of Brackish Groundwater by Using a Polypiperazine Membrane - Galanakis, Charis M.; Fountoulis, Georgios; Gekas, Vassilis (My University, 2012)
The purpose of the current study is to investigate the nanofiltration of brackish groundwater by using a polypiperazine membrane. The latter is a polymeric three-layer thin film with an active layer of semi-aromatic/aliphatic polyamide. Particularly, samples of different hardness and salinity values (up to 762mg CaCO 3 and 1803mg NaCl/L, respectively) were collected and treated under low transmembrane pressures (6-10bar), in a cross-flow nanofiltration module. Desalination monitoring was performed by determining performance parameters, total hardness and salinity retention coefficients of brackish samples during experiments. According to the results, the tested membrane was able to provide high hardness retention coefficients (70-76%), satisfactory permeate fluxes (15-47L·m -2·h -1) and high mineral fouling resistance (flux recovery values between 93 and 98%). A disadvantage of the process was the relatively low removal of salinity (44-66% for brackish groundwaters) that restricts the application in samples possessing salinity not much higher than ~1100mg NaCl/L. Finally, the retention of divalent and monovalent ions was governed by size effect and ion valance, probably due to the high ionic conditions of brackish samples and the poly-ampholytic nature of the membrane
Keywords: Nanofiltration; Calcium carbonate; Groundwater; Hardness; Water--Purification--Filtration; Wells